2015
DOI: 10.1017/s0021859615001082
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-limited light use efficiency in wheat crop simulators: comparing three model approaches

Abstract: SUMMARYThree different explanatory indicators for reduced light use efficiency (LUE) under limited nitrogen (N) supply were evaluated. The indicators can be used to adapt dry matter production of crop simulators to N-limited growth conditions. The first indicator, nitrogen factor (NFAC), originates from the CERES-Wheat model and calculates the critical N concentration of the shoot as a function of phenological development. The second indicator, N nutrition index (NNI), calculates a critical N concentration as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Variation in nitrogen dilution curves for wheat has been reported that relates to phenological development, hence the attempts to model critical nitrogen against phenological stage ( Angus, 2007 ; Yue et al, 2012 ; Zhao et al, 2014 ; Ratjen and Kage, 2016 ). Variation in allometric relations, between organs as well as between structural and labile carbohydrates, partially underlies the effect of phenology on nitrogen dilution curves ( Gastal et al, 2015 ; Hoogmoed and Sadras, 2016 ; Yan et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Variation in nitrogen dilution curves for wheat has been reported that relates to phenological development, hence the attempts to model critical nitrogen against phenological stage ( Angus, 2007 ; Yue et al, 2012 ; Zhao et al, 2014 ; Ratjen and Kage, 2016 ). Variation in allometric relations, between organs as well as between structural and labile carbohydrates, partially underlies the effect of phenology on nitrogen dilution curves ( Gastal et al, 2015 ; Hoogmoed and Sadras, 2016 ; Yan et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…R Foundation for Statistical Computing, Vienna, Austria). Results of this approach have been implemented at the HumeWheat crop-soil model, which has been designed for the detection of interannual variability in N fertilization demand (Ratjen 2012, Ratjen andKage 2015b).…”
Section: Introductionmentioning
confidence: 99%